CORRELATION BETWEEN SERUM TESTOSTERONE, BIOCHEMICAL AND CLINICAL MARKERS IN PROSTATE CANCER PATIENTS - Bogdan Roussev; Petar Kosev; Alexander Hinev; Bistra Galunska (Peytchinski Publishing, 2016)
Purpose: Androgens seems to play an important role in prostate cancer (PCa) pathogenesis. Some studies reveal that possible testosterone deficiency could be involved in PCa development and progress. Others indicate that men with high testosterone levels have increased risk in developing more aggressive PCa and poor response to therapy. The objective of the present study is to establish a possible correlation between serum total testosterone levels (TT), prostate specific antigen (PSA) and clinical markers evaluating the aggressiveness of the tumor process in PCa patients. Material/Methods: A total of eighty males, aged from 52 to 84 years (mean age 66.28 ± 6.015 years), with histologically confirmed PCa, entered the study. Diagnosis of PCa was established by systemic transrectal ultrasound-guided tru-cut prostate biopsies (10 cores at least). Detected tumors were graded using the Gleason grading system. Serum TT and PSA were analyzed immunochemically. Pearson correlation statistics with a level of significance set at p < 0.05 was used for data analysis. Results: Strong significant positive correlation (Pearson r=0.90, p<0.01) between PSA and testosterone levels was found in lowest risk group. For the highest risk group there was a negative association between the same parameters (Pearson r=-0.38, p<0.05). A relatively weak positive relationship (Pearson r = 0.29) was detected for patients with less aggressive tumors (Gleason score <7) and a negative trend (Pearson r = -0.27) in patients with highly aggressive prostate cancer (Gleason >7). Conclusions: Our results confirm the hypothesis that low testosterone levels are related to poor prognosis and increased severity of PCa.